Banjar Tribe's View on the Ethnobotanical Value of Pineapple Plants in Tamban Catur - Norfajrina, Norfajrina (Proceeding International Conference on Religion, Science and Education, 2025)
The pineapple plant (Ananas comosus) that has been cultivated by the Tamban Catur community is mostly only consumed and traded so that the potential benefits of pineapple plants have not been fully utilised and understood by the community, especially the current generation. Therefore, this study focuses on the ethnobotanical value of pineapple plants in Tamban Catur. Research was conducted by describing local knowledge about the use, benefits, and cultural context related to pineapple plants in the daily lives of people in Tamban Catur. This study aims to reveal the urgency of the ethnobotanical value of pineapple plants in Tamban Catur and its implications in maintaining traditions amid the dynamics of changing times. Field surveys and structured interviews with local residents collected data on traditional uses, treatments, and cultural views related to pineapple plants. The research results show the crucial role of pineapple plants in various aspects of Tamban Catur people's lives including in the culinary field, health, and even in the implementation of local ceremonies and traditions. This paper provides an in-depth understanding of the importance of the pineapple plant in the context of cultural heritage and local knowledge, while supporting efforts to preserve traditional knowledge in the modern era.